L’ombra di Cicerone, da Operation Cicero a Spartacus - Cicero's Shadow from Operation Cicero to Spartacus - Mancino, Anton Giulio (Ciceroniana On Line, 2020)
The article examines the representation and use of the figure of Cicero in two films by Joseph L. Mankiewicz, Julius Caesar and Five Fingers, and in Stanley Kubrick’s Spartacus. By comparing these films with the original theatrical and literary sources on which they are based, I argue that Cicero’s appearance and disappearance in these films is linked to the US historical context, in particular McCarthyism and the notorious “black list”. L’articolo verte sull’uso allusivo, strategico o trasversale, giocando sulla presenza/assenza della figura storica di Cicerone in due film chiave di Joseph Leo Mankiewicz, Julius Caesar e Five Fingers, e in uno di Stanley Kubrick, Spartacus. Attraverso i rispettivi testi teatrali o letterari di partenza il personaggio di Cicerone compare e scompare dentro contesti storici legati principalmente negli Stati Uniti al maccartismo e alla famigerata “lista nera”. L’article traite de l’usage allusif, stratégique ou transversal, de la figure historique de Cicéron, en jouant sur sa présence ou son absence, dans deux films de Joseph Leo Mankiewicz, Julius Caesar et Five Fingers, ainsi qu’un film de Stanley Kubrick, Spartacus. À travers les textes théâtraux et littéraires qui en sont les sources, le personnage de Cicéron apparaît et disparaît dans des contextes historiques étatsuniens liés au maccarthysme et à la tristement célèbre blacklist.